A questão étnico-racial na graduação em Serviço Social: perspectivas a partir do ensino privado no centro-oeste paulista - Ramos, Vanessa Isabella dos Santos (2023)
This master's research focused on studying the ethnic-racial issue in graduation in social work in the center-west of São Paulo. It aimed to understand whether undergraduate training in social work at private institutions offers an anti-racist education. As a hypothesis, it indicated that private schools are not training professionals with an education focused on Ethnic-Racial Relations in which racism is problematized from a critical and explicitly antiracist pedagogical proposal, as advocated by current laws and documents. Documentary research was used to analyze Pedagogical Projects of Social Service Courses in Academic Training Units offering private education in the Administrative Region of Bauru/SP. The study showed that in this region, the private institutions that offer higher education in social work do not offer, in their pedagogical proposals, training based on education for Ethnic-Racial Relations in an anti-racist perspective that runs through both teaching, research and extension. Also, there are no disciplines in their curriculum that deal with education for Ethnic-Racial Relations, as guided by the Brazilian Association of Teaching and Research in Social Work, leaving the racial theme only to the disciplines that make up the Minimum Curriculum of Social Work. It was concluded, therefore, that a debate is needed to update the Pedagogical Projects of Social Service Courses that contemplate the discussion and inclusion of the ethnic-racial agenda, overcoming this issue in professional academic training